Efektivitas Edukasi dan Sosialisasi Anti-Perundungan oleh Mahasiswa dalam Studi pada Pelajar SD - Hisny Fajrussalam; Annisa Salsabila Nurista; Elvara Salsabilla Chaisa; Gandes Rahmi Mahayun Sari; Lisda Pariha; Nurul Aini; Putri Laura Nugraha; Zhaharani Alfiah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Bullying remains a frequent issue in Indonesia, particularly among elementary school students. This study aims to describe the effectiveness of anti-bullying educational and socialization activities carried out by students of the P3K Program at the Indonesia University of Education in an elementary school in Purwakarta. The background of this research is the increasing cases of bullying—both direct and digital—which negatively affect students' social and emotional development. This study employed a descriptive quantitative method involving fourth-, fifth-, and sixth-grade students as research subjects. Data were collected through the Secret Box during the pre- and post-activity stages, as well as through documentation of educational activities such as poster competitions, educational video screenings, and socialization sessions. The findings indicate an improvement in students’ understanding of the definition, forms, and impacts of bullying, along with the development of empathy, social awareness, and commitment to respectful behavior. Moreover, creative and participatory approaches proved effective in engaging students actively, allowing anti-bullying messages to be more easily understood and internalized. Therefore, the anti-bullying education and socialization program, supported through collaboration among university students, teachers, and pupils, is proven effective in enhancing students’ comprehension while fostering a safer and more inclusive school culture.